TATALAKSANA HEPATIC ENCEPHALOPATHY - Lidia Dewi; Elvi Fitraneti (Nusantara Hasana Journal, 2026)
Hepatic encephalopathy (HE) is a neuropsychiatric syndrome resulting from impaired liver function, most commonly occurring in patients with liver cirrhosis or acute liver failure. The condition is characterized by a broad spectrum of clinical manifestations, ranging from subtle cognitive impairment to altered consciousness and coma. The primary pathogenesis of HE is associated with the accumulation of ammonia and other neurotoxic substances that cannot be adequately metabolized by the diseased liver, leading to central nervous system dysfunction. This review aims to examine the current management strategies for hepatic encephalopathy based on recent scientific evidence. The method employed was a literature review of scientific journals addressing the diagnosis, treatment, and prevention of HE recurrence. The findings indicate that identifying and correcting precipitating factors, such as infections, gastrointestinal bleeding, constipation, electrolyte disturbances, and the use of certain medications, are fundamental components of management. Pharmacological therapy primarily involves lactulose as the first-line treatment to reduce ammonia levels, while rifaximin is commonly used as an adjunctive therapy to prevent recurrence. Adequate nutritional support, including appropriate protein intake, also plays a significant role in improving patient outcomes. In severe or recurrent cases, liver transplantation may serve as the definitive treatment option. A comprehensive and multidisciplinary approach to the management of hepatic encephalopathy can reduce morbidity, prevent recurrence, and improve patients’ quality of life.